Genetic divergence and interaction among CUPRAC, FRAP and total phenolics content in cauliflower (Brassica oleracea var. botrytis L.) - Dey, S.S.; Dey, R. Bhatia; Sharma, Saharsh; Sharma, Kanika; Kumar, Raj; Sharma, V.K.; Prakash, Chander (The Indian Journal of Genetics and Plant Breeding, 2016)
Antioxidant capacity and total phenolics content were estimated in 46 cauliflower lines to determine genetic variability, heritability and correlation among them with the objective to formulate breeding strategies for development cultivars with higher antioxidant capacity.The genotypes comprised of six CMS lines, few advance breeding lines and other core collection of our institute. Significant variability was recorded for CUPRAC, FRAP and total phenolics content indicating the scope for improvement in these traits based on various breeding strategies. Phenotypic co-efficient of variation (PCV) was higher (43.01, 73.07 and 64.28) than genotypic co-efficient of variation (GCV) (41.34, 71.83 and 63.88) in all cases indicating the role of environment in expression of these traits. However improvement for these traits is possible through selection and heterosis breeding as broad sense heritability (92.44% to 98.75%) and genetic advance as percentage of mean (82.46% to 130.87%) was high for all the traits. Correlation coefficient analysis revealed that CUPRAC, FRAP and total phenolics had significant positive correlation among each other.However,none of them had any significant correlation with marketable yield. Fourty six genotypes were classified into 6 groups based on non-hierarchical cluster analysis and phenotypic divergence. This study will pave the way for breeding of cauliflower cultivars and hybrids with higher antioxidant capacity and phenolics content